Nitrogen‐doped Porous Carbon Obtained from Silk Cocoon for High Performance Li‐O2 Batteries. Issue 25 (4th July 2019) - Liu, Jiuqing; Zhao, Haijun; Zhu, Fangfang; Yu, Wanjing; Li, Jie; Li, Qihou; Wang, Cheng
Abstract: Nitrogen‐doped porous carbon obtained from silk cocoon (NCFC) was first used as cathodes for Li‐O2 batteries with ionic liquid in this paper. NCFC is made up of irregular bending slices and has a high specific discharge product of most Li‐O2 surface area of 2142.0 m 2  g −1 which means numerous active sites for electrochemical reactions. The results show that NCFC based Li‐O2 battery has good cycle stability and high energy efficiency under different current density. In particular, NCFC based Li‐O2 batteries can work more than 400 cycles (500 mAh g −1 at 0.20 mA cm −2 ) with the maximum overpotential less than 0.92 V, which is much better than super P based Li‐O2 batteries (188 cycles with overpotential up to 1.88 V) and many reported Li‐O2 batteries. The results show that NCFC is a very promising material for Li‐O2 batteries. Abstract : A nitrogen‐doped porous carbon composed of bending slices is obtained by carbonization and activation of silkworm cocoons. It has a specific surface area of 2142 m 2  g −1 . The lithium air battery assembled with this carbon material has excellent cycle performance. When the current density is 0.2 mA cm −2 and the fixed capacity is 500 mAh g −1, it can work stably for more than 400 cycles and the maximum overpotential is only 0.92 V.